El Excentrico, 1956-09-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
September 5, 1956 [5 de septiembre de 1956]. Ano 7, No. 1. Cover contains a photo of Linda Villalobos, who has won the title of queen of the Council of Civic Coordination's court of honor. The headline reads, "Su Graciosa Majested Linda Villalobos" (transl: Her Graceful Majesty).